2021
DOI: 10.1016/j.advwatres.2021.103857
|View full text |Cite
|
Sign up to set email alerts
|

Hyporheic exchanges due to channel bed and width undulations

Abstract: Riffle-pool sequences are fundamental, ubiquitous morphological features of alluvial rivers that are thoroughly studied in general and commonly incorporated into river restoration projects. Most previous investigations on the effect of riffle-pool sequences on hyporheic exchanges focused on solely bed undulation, because that is widely thought to be the defining feature of riffle-pool sequences. However, riffle-pool sequences also have significant width undulations that are vital to riffle-pool sequences morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 87 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…In fact, the HE induced by pool‐riffle bedforms and meanders could have similar magnitude and scale as that induced by other mechanisms, such as bars, steps, dams, channel width undulations, etc. (Buffington & Tonina, 2009; Hester & Doyle, 2008; Kasahara & Hill, 2006; Movahedi et al., 2021). This can be associated to the fact that these features generally have relatively large sizes and could strongly influence the surface flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the HE induced by pool‐riffle bedforms and meanders could have similar magnitude and scale as that induced by other mechanisms, such as bars, steps, dams, channel width undulations, etc. (Buffington & Tonina, 2009; Hester & Doyle, 2008; Kasahara & Hill, 2006; Movahedi et al., 2021). This can be associated to the fact that these features generally have relatively large sizes and could strongly influence the surface flow.…”
Section: Introductionmentioning
confidence: 99%
“…However, the model did not include the pool‐riffle topography. The interactions among surface flow, riffles, and meanders are common and essential to HE processes in pool‐riffle streams, which is thus vital to the studies in redox and nitrogen dynamics in HZ and river design during river restorations (Marzadri et al., 2012; Movahedi et al., 2021; Stonedahl et al., 2013; Tonina, 2005; Trauth et al., 2013). However, a comprehensive study of the hyporheic flow in a pool‐riffle system that considers both various meanders and pool‐riffle bedforms is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, the same GCS has been found to be an important control on river hyporheic exchange rates (Movahedi et al, 2021), so the methodology is relevant beyond just morphodynamics.…”
Section: Geomorphic Covariance Structure (Gcs) and Landformsmentioning
confidence: 99%
“…Few studies compared the engineered interventions to natural morphological features (Smidt et al 2015;Morén et al 2017;Hester et al 2018) and reported higher overall flux induced due to engineered structures. Recent studies at bedform scale have highlighted the importance of streambed heterogeneity, bed and width undulations in case of hyporheic response to modification studies Movahedi et al 2021) where the sediment architecture was often more influential than channel morphology in case of highly heterogeneous streambeds . Advancement in computing capabilities enabled numerical simulation and optimization studies of design structures (rock-vanes, weirs) for stream restoration and enhanced nitrogen removal (Khosronejad et al 2018;Liu & Chui 2020).…”
Section: Feature Modificationsmentioning
confidence: 99%